Apatite microflotation using pequi oil. (3rd September 2015) - Silva, A. C.; Silva, E. M. S.; Silva, T. C.; Alves, B. E.
Abstract : Pequi ( Caryocar brasiliense ) is a Brazilian oleaginous fruit, rich in fatty acids, with a predominance of oleic and palmitic acids. The fruit is composed of three major parts: the outer mesocarp (or white pulp), the inner mesocarp (or yellow pulp), which is very appreciated in the local cuisine, and the nut. The oil extracted from the nut (43.59 ± 0.16 oleic and 43.76 ± 0.04% palmitic acids) or from the yellow pulp (55.87 ± 0.30 oleic and 35.17 ± 0.27% palmitic acids) are used not only for nourishment but also as a medicinal product and in cosmetic formulations. The white pulp does not have any commercial application being a residue. This paper proposes to use the oil from pequi's yellow pulp as a collector in apatite microflotation, due to its rich fatty acid composition. The oil was saponified with NaOH and then applied in microflotation tests using a modified Hallimond tube and pure samples of apatite. The results indicate that pequi's yellow pulp oil can be used as a collector in the froth flotation of this mineral (recovery >95% for concentrations between 5 and 15 mg L − 1 ).